2002
DOI: 10.1080/090647002320229365
|View full text |Cite
|
Sign up to set email alerts
|

Catheterization of Arteria Epigastrica Cranialis, Measurement of Nutrient Arteriovenous Differences and Evaluation of Daily Plasma Flow Across the Mammary Gland of Lactating Sows

Abstract: Catheterization of arteria epigastrica cranialis, measurement of nutrient arteriovenous differences and evaluation of daily plasma ow across the mammary gland of lactating sows.The objectives of the present study were: (i) to evaluate a novel procedure for catheterization of the mammary artery; (ii) to measure amino acid, glucose and calcium arteriovenous differences in lactating sows; and (iii) to evaluate the use of different markers in estimating mammary plasma ow by the Fick principle. Five multiparous sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Plasma:milk values as high as 1,050 and 858 were also reported when lysine and methionine, respectively, were used as internal markers (Nielsen et al, 2002a, Table 14.1). These values raise questions when considering the reported low average daily milk production of 7.4 kg for a litter size of 12 (Nielsen et al, 2002a). In that same study, when calcium was used as marker, the average plasma flow was 2.8 l/min, a value falling within the reported range.…”
Section: Estimating Mammary Blood Flowmentioning
confidence: 90%
See 1 more Smart Citation
“…Plasma:milk values as high as 1,050 and 858 were also reported when lysine and methionine, respectively, were used as internal markers (Nielsen et al, 2002a, Table 14.1). These values raise questions when considering the reported low average daily milk production of 7.4 kg for a litter size of 12 (Nielsen et al, 2002a). In that same study, when calcium was used as marker, the average plasma flow was 2.8 l/min, a value falling within the reported range.…”
Section: Estimating Mammary Blood Flowmentioning
confidence: 90%
“…Unlike amino acids, calcium is not metabolized hence (Farmer et al, 2008b). Guan et al (2004a) Fick (lysine) 11 4.5 11.4 560 Guan et al (2004b) Fick (lysine) 11 3.6 10.7 490 Linzell et al (1969a) 2 Fick ( 3 HO) 6 1.9 3 6.2 441 3 Nielsen et al 2002bFick (lysine) 8 3.2 10 550 Nielsen et al 2002aFick (lysine) 12 5.5 7.4 1,050 Nielsen et al (2002a) Fick (methionine) 12 4.4 7.4 858 Nielsen et al (2002a) Fick (calcium) 12 2.8 7.4 548 Renaudeau et al (2002) Flow probe 12 3.6 3 11 471 3 Renaudeau et al 2002Fick (lysine) 12 3.9 4 11 511 Trottier et al (1997) Fick (lysine) 11 3.0 8.1 541…”
Section: Estimating Mammary Blood Flowmentioning
confidence: 99%
“…Both Nielsen et al (2002a) and Dourmad et al (2000) showed a positive mammary AVD for calcium, and Dourmad et al (2000) also noted a positive uptake of phosphorus, with its AVD across mammary tissue increasing after a meal. However, the extraction rates of calcium and phosphorus from arterial blood (4.1 and 3.1%, respectively) were much lower than those of other major nutrients (ranging from 20 to 35%).…”
Section: Uptake Of Other Energetic Precursors By the Sow Mammary Glandsmentioning
confidence: 93%
“…Plasma:milk ratios of 1050 and 858 using lysine and methionine, respectively, as internal markers were also reported (Nielsen et al 2002a, Table 1). These high ratios and corresponding plasma flow rate values raise questions when considering the reported low average daily milk production of 7.4 kg for a litter size of 12 (Nielsen et al 2002a). On the other hand, when, in that same study, calcium was used as marker, an average plasma flow value of 40599747 L d…”
Section: Farmer Et Al * the Lactating Sow's Mammary Glands 197mentioning
confidence: 99%
See 1 more Smart Citation